2D and 3D silver-based coordination polymers with thiomorpholine-4-carbonitrile and piperazine-1, 4-dicarbonitrile: structure, intermolecular interactions, photocatalysis, and thermal behavior. Issue 27 (23rd June 2021) - Ristić, Predrag; Filipović, Nenad; Blagojević, Vladimir; Ćirković, Jovana; Holló, Berta Barta; Đokić, Veljko R.; Donnard, Morgan; Gulea, Mihaela; Marjanović, Ivana; Klisurić, Olivera R.; Todorović, Tamara R.
Abstract : The reaction of the thiomorpholine-4-carbonitrile and piperazine-1, 4-dicarbonitrile ligands afforded four Ag(i ) coordination polymers with excellent photocatalytic activity in the degradation of the mordant blue 9 dye. Abstract : Four silver-based coordination polymers, {[Ag(L1)2 ]NO3 }∞ (1 ), {[Ag(L1)2 ]ClO4 }∞ (2 ), {[Ag(L2)2 ]NO3 ·H2 O}∞ (3 ) and {[Ag(L2)2 ]ClO4 }∞ (4 ), were synthesized using the thiomorpholine-4-carbonitrile (L1) and piperazine-1, 4-dicarbonitrile (L2) ligands. Compounds 1 and 2 are two-dimensional, while 3 and 4 are three-dimensional. L1 and L2 are 1, 4-bis-monodentate ligands in all compounds, while Ag(i ) ions are four-coordinated in a slightly distorted tetrahedral geometry. Topological analysis in standard representations suggests that underlying nets in 1 and 2 have an sql topology, while 3 and 4 exhibit a dia topology. Thermal analysis shows that 3 loses crystalline water at room temperature, while other compounds show good thermal stability. All compounds show good photocatalytic activity for photocatalytic degradation of the mordant blue 9 dye, with reaction rates in the range 0.029 to 0.061 min −1 . The best result was obtained for compound 4, which can be correlated to its largest lattice volume.